Using Vlog to Improve Speaking Skills of the Eleventh Grade Students of Senior High School - Amri, Hasrawati; Mochtar Marhum; Maf'ulah; Nur Sehang Thamrin (Institut Agama Islam Negeri Palopo, 2025)
The objective of this research is to find out whether using vlog can improve the speaking skills of the eleventh grade students of SMAN 5 Palu. This research applied quasi-experimental research design. The sample of this research were the eleventh grade IPA 1 and IPA 4 consist 33 students. The sample were selected by using purposive sampling. The data were collected by administering a speaking test conducted before and after treatment, or pre-test and post-test. The data were analyzed using t-test to compare mean score of pre-test and post-test of experimental and control class. The result showed that the mean differences of the experimental and control class were (46.67) and (51.21). While the post-test were (75.76) and (56.97). Further analysis indicates, t-counted (13.43) is greater than t-table (1.670). There was improvement of the students speaking skill. It is conclude that the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. It means that using vlog give good effect in improve students speaking skill of SMAN 5 Palu.